Pretreatment method and manufacture method of cross section evaluation sample
The method of forming a metal sintering layer on the cross-sectional sample surface addresses the issue of abnormal signals, enhancing evaluation accuracy and preventing damage, thus improving electron microscopy analysis.
Patent Information
- Application Number
- JP2023117389
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-30
AI Technical Summary
Conventional methods for creating cross-sectional samples for electron microscopy face challenges in blocking abnormal signals due to thin vapor films, leading to difficulties in accurate evaluation.
A method involving the preparation of a structure with a metal sintering layer formed by sintering a paste material containing metal nanoparticles, which is then polished to create an evaluation target surface, effectively shielding abnormal signals.
Reduces the detection of abnormal signals during evaluation, maintaining signal integrity and preventing surface damage, while ensuring high spatial resolution.
Smart Images

Figure 2025014654000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a pretreatment method and a method for preparing a cross-sectional evaluation sample. [Background technology]
[0002] As one method for preparing a sample for cross-sectional observation by a scanning electron microscope, a method for forming a vapor-deposited film on a surface adjacent to the cross-section of the sample is known. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 5-3012 Summary of the Invention [Problem to be solved by the invention]
[0004] In conventional methods, the thickness of the deposited film is so thin that it is difficult for the deposited film to adequately block abnormal signals generated on the surface of the sample when observing the cross section of the sample.
[0005] An object of the present disclosure is to provide a pretreatment method and a method for preparing a cross-section evaluation sample that can reduce the amount of abnormal signals detected when evaluating a surface to be evaluated. [Means for solving the problem]
[0006] The pretreatment method disclosed herein includes the steps of preparing a structure having a first surface and a second surface connected to the first surface, applying a paste material containing metal nanoparticles onto the first surface, sintering the paste material applied onto the first surface to form a metal sintered layer, and polishing the second surface of the structure on which the metal sintered layer is formed to form a surface to be evaluated. Effect of the Invention
[0007] According to the present disclosure, it is possible to provide a pretreatment method and a method for preparing a cross-section evaluation sample that can reduce the amount of abnormal signals detected when evaluating a surface to be evaluated. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a perspective view showing a cross-section evaluation sample according to an embodiment. [Diagram 2] FIG. 2 is a perspective view (1) showing a method for producing a cross-section evaluation sample according to an embodiment. [Diagram 3] FIG. 3 is a perspective view (2) showing the method for producing a cross-section evaluation sample according to the embodiment. [Figure 4] FIG. 4 is a perspective view (3) showing the method for producing a cross-section evaluation sample according to the embodiment. [Diagram 5] FIG. 5 is a perspective view (4) showing a method for producing a cross-section evaluation sample according to an embodiment. [Figure 6] FIG. 6 is a perspective view (5) showing a method for producing a cross-section evaluation sample according to an embodiment. [Figure 7] FIG. 7 is a perspective view (6) showing a method for producing a cross-section evaluation sample according to an embodiment. [Figure 8] FIG. 8 is a schematic diagram for explaining a signal emitted when a cross-section evaluation sample having a metal sintered layer formed on the surface is irradiated with an electron beam. [Figure 9] FIG. 9 is a schematic diagram for explaining a signal emitted when a cross-section evaluation sample having a metal paste layer formed on its surface is irradiated with an electron beam. [Figure 10] FIG. 10 is a schematic diagram for explaining a signal emitted when an electron beam is irradiated onto a cross-section evaluation sample having a metal thin film formed on its surface by a vapor deposition method or a sputtering method. [Figure 11] FIG. 11 is a diagram showing the evaluation results of a cross-section evaluation sample having a metal sintered layer formed on the surface. [Figure 12] FIG. 12 is a diagram showing the evaluation results of a cross-section evaluation sample having a metal paste layer formed on the surface. [Figure 13] FIG. 13 is a graph comparing the band edge emission intensities. [Figure 14] FIG. 14 is a graph comparing the CL spectra. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The embodiments for carrying out the invention are described below.
[0010] [Description of the embodiments of the present disclosure] First, the embodiments of the present disclosure will be described. In the following description, the same or corresponding elements are denoted by the same reference numerals, and the same description thereof will not be repeated.
[0011] [1] A pretreatment method according to one embodiment of the present disclosure includes the steps of preparing a structure having a first surface and a second surface connected to the first surface, applying a paste material containing metal nanoparticles onto the first surface, sintering the paste material applied onto the first surface to form a metal sintered layer, and polishing the second surface of the structure on which the metal sintered layer is formed to form an evaluation target surface. In this case, when the evaluation target surface is evaluated, signals generated on the first surface can be shielded. Therefore, the amount of abnormal signals detected when evaluating the evaluation target surface can be reduced.
[0012] [2] In the above [1], the thickness of the metal sintered layer may be 1 μm or more. In this case, the amount of abnormal signals detected is easily reduced.
[0013] [3] In the above [1] or [2], the metal nanoparticles may contain at least one of gold, silver, chromium, cobalt, copper, iron, palladium, platinum, tantalum, tin, titanium, and zinc. Metal nanoparticles containing these metals are easily available.
[0014] [4] A method for preparing a cross-section evaluation sample according to another embodiment of the present disclosure includes the steps of: preparing a structure having a first surface and a second surface connected to the first surface; applying a paste material containing metal nanoparticles onto the first surface; sintering the paste material applied onto the first surface to form a metal sintered layer; and polishing the second surface of the structure on which the metal sintered layer is formed to form an evaluation target surface. In this case, when the evaluation target surface is evaluated, signals generated on the first surface can be shielded. Therefore, the amount of abnormal signals detected when evaluating the evaluation target surface can be reduced.
[0015] [5] In the above [4], the cross-section evaluation sample may be used to evaluate a chemical state of the second surface by irradiating it with an electron beam, in which case the amount of abnormal signals detected when evaluating the chemical state of the second surface can be reduced.
[0016] [Details of the embodiment of the present disclosure] Hereinafter, embodiments of the present disclosure will be described in detail, but the present disclosure is not limited thereto.
[0017] (Cross-section evaluation sample) A cross-section evaluation sample 1 according to the embodiment will be described with reference to Fig. 1. Fig. 1 is a perspective view showing a cross-section evaluation sample 1 according to the embodiment.
[0018] The cross-section evaluation sample 1 is a sample used to evaluate the chemical state of a cross-section by, for example, irradiating it with an electron beam. Methods for evaluating the chemical state of a cross-section by irradiating it with an electron beam include, for example, cathodoluminescence (CL) method, Auger electron spectroscopy, soft X-ray emission spectroscopy, and electron probe microanalysis. The cross-section evaluation sample 1 may be a sample used for structural observation of a cross-section by a scanning electron microscope (SEM). The cross-section evaluation sample 1 may be a sample used for elemental analysis by an energy dispersive X-ray analyzer. As shown in FIG. 1, the cross-section evaluation sample 1 has a structure 10, a metal sintered layer 20, and a metal sheet 30.
[0019] The structure 10 has a surface 10a. The structure 10 includes a substrate 11 and an evaluation target film 12. In this embodiment, the substrate 11 is a silicon carbide (SiC) substrate. The evaluation target film 12 is provided on the substrate 11. In this embodiment, the evaluation target film 12 is a gallium nitride (GaN) film. The evaluation target film 12 constitutes the surface 10a. Note that the substrate 11 may be any bulk material and is not limited to a silicon carbide substrate. The evaluation target film 12 is not limited to a gallium nitride film, and may be an indium phosphide (InP) film or a gallium arsenide (GaAs) film.
[0020] The metal sintered layer 20 is provided on the structure 10. The metal sintered layer 20 contacts the surface 10a of the structure 10. The thickness of the metal sintered layer 20 is, for example, 1 μm or more and 10 μm or less. If the thickness of the metal sintered layer 20 is less than 1 μm, the abnormal signal may not be reduced completely, but if the thickness of the metal sintered layer 20 is 1 μm or more, the amount of abnormal signals detected is easily reduced. Even if the thickness of the metal sintered layer 20 is made larger than 10 μm, the effect of reducing the abnormal signal is not much different from when the thickness of the metal sintered layer 20 is about 1 μm, and the manufacturing effort and cost increase. The metal sintered layer 20 contains at least one metal selected from the group consisting of gold (Au), silver (Ag), chromium (Cr), cobalt (Co), copper (Cu), iron (Fe), palladium (Pd), platinum (Pt), tantalum (Ta), tin (Sn), titanium (Ti), and zinc (Zn). Metal nanoparticles containing these metals are easy to obtain. In this embodiment, the metal sintered layer 20 is a silver sintered layer. The structure 10 and the metal sintered layer 20 constitute an evaluation target surface 1a, which is a cross section to be evaluated.
[0021] The metal sheet 30 is provided on the metal sintered layer 20. The metal sheet 30 is, for example, an aluminum sheet. The metal sheet 30 does not necessarily have to be provided.
[0022] (Method of preparing cross-sectional evaluation samples) A method for producing the cross-section evaluation sample 1 according to the embodiment will be described with reference to Fig. 2 to Fig. 7. Fig. 2 to Fig. 7 are perspective views showing the method for producing the cross-section evaluation sample 1 according to the embodiment.
[0023] First, as shown in FIG. 2, a structure 10 is prepared. The structure 10 has a surface 10a and a side surface 10b continuous with the surface 10a. The structure 10 includes a substrate 11 and a film 12 to be evaluated. In this embodiment, the substrate 11 is a silicon carbide substrate. The film 12 to be evaluated is provided on the substrate 11. In this embodiment, the film 12 to be evaluated is a gallium nitride film. The film 12 to be evaluated constitutes the surface 10a. The substrate 11 and the film 12 to be evaluated constitute the side surface 10b.
[0024] Next, as shown in FIG. 3, a paste material 21 containing metal nanoparticles is applied onto the structure 10. The application of the paste material 21 is performed, for example, with the surface 10a of the structure 10 facing upward. The metal nanoparticles contain at least one metal selected from the group consisting of gold, silver, chromium, cobalt, copper, iron, palladium, platinum, tantalum, tin, titanium, and zinc. Metal nanoparticles containing these metals are easily available. In this embodiment, the paste material 21 is a silver paste containing silver nanoparticles.
[0025] Next, as shown in FIG. 4, the structure 10 is turned over so that the surface 10a on which the paste material 21 is applied faces downward.
[0026] 5, the structure 10 is pressed onto the metal sheet 30. This causes the paste material 21 to spread over a wide area of the surface 10a, and improves the adhesion between the structure 10 and the paste material 21. In this embodiment, the metal sheet 30 is an aluminum sheet.
[0027] Next, as shown in FIG. 6, the paste material 21 is sintered to form the metal sintered layer 20. The sintering is performed by heating in an inert gas atmosphere such as nitrogen gas. In this embodiment, the sintering temperature is 210° C., and the sintering time is 60 minutes. The thickness of the metal sintered layer 20 is, for example, 1 μm or more. In this case, it is easy to reduce the amount of abnormal signals detected.
[0028] Next, as shown in Fig. 7, the side surface 10b of the structure 10 on which the metal sintered layer 20 is formed is polished to form the evaluation surface 1a. The polishing may be mechanical polishing, argon sputtering, or a combination of these. In this manner, the cross-section evaluation sample 1 can be prepared.
[0029] According to the embodiment, after forming the metal sintered layer 20 on the surface 10a of the structure 10, the side surface 10b of the structure 10 is polished to form the evaluation target surface 1a. In this case, when evaluating the evaluation target surface 1a, the signal generated on the surface 10a can be shielded by the metal sintered layer 20. Therefore, the amount of abnormal signals detected when evaluating the evaluation target surface 1a can be reduced. In addition, since the sputtering method is not used when forming the metal sintered layer 20, damage near the surface 10a can be suppressed.
[0030] The mechanism by which the amount of abnormal signals detected during evaluation of the evaluation target surface 1a can be reduced is believed to be as follows.
[0031] 8 is a schematic diagram for explaining a signal S emitted when an electron beam EB is irradiated to a cross-section evaluation sample 1 having a metal sintered layer 20 formed on a surface 10a. As shown in FIG. 8, when an electron beam EB is irradiated to an evaluation target surface 1a, a signal S is generated from the surface 10a of the structure 10 in addition to the evaluation target surface 1a. When a metal sintered layer 20 is formed on the surface 10a, the signal S generated on the surface 10a is blocked by the metal sintered layer 20. Therefore, the amount of abnormal signals detected can be reduced.
[0032] FIG. 9 is a schematic diagram for explaining a signal S emitted when an electron beam EB is irradiated to a cross-section evaluation sample 8 having a metal paste layer 80 formed on a surface 10a. As shown in FIG. 9, there are many gaps in the metal paste layer 80. Therefore, when an electron beam EB is irradiated to an evaluation target surface 8a of the cross-section evaluation sample 8, a part of the signal S generated on the surface 10a passes through the metal paste layer 80 without being blocked by the metal paste layer 80. Therefore, it is difficult to sufficiently reduce the amount of abnormal signals detected. In addition, the electron beam EB irradiated to the cross-section evaluation sample 8 is scattered by the grains (gaps) of the metal paste layer 80, deteriorating the spatial resolution.
[0033] FIG. 10 is a schematic diagram for explaining a signal S emitted when an electron beam EB is irradiated to a cross-section evaluation sample 9 having a metal thin film 90 formed on a surface 10a by a vapor deposition method or a sputtering method. As shown in FIG. 10, the metal thin film 90 formed by a vapor deposition method or a sputtering method is generally thin. Therefore, when an electron beam EB is irradiated to an evaluation target surface 9a of the cross-section evaluation sample 9, a part of the signal S generated on the surface 10a passes through the metal thin film 90 without being blocked by the metal thin film 90. Therefore, it is difficult to sufficiently reduce the amount of abnormal signals detected. In addition, when the metal thin film 90 is formed on the surface 10a by a sputtering method, damage D may occur near the surface 10a, making it impossible to detect the desired characteristics. It is possible to thicken the metal thin film 90, but this requires a huge amount of time and cost.
[0034] (Evaluation Results) First, a cross-section evaluation sample 1 having a metal sintered layer 20 formed on the surface 10a of a structure 10 was prepared by the method for preparing a cross-section evaluation sample 1 according to the embodiment. The cross-section evaluation sample 1 has a substrate 11 and a film 12 to be evaluated. The film 12 to be evaluated is a gallium nitride film. The thickness of the film 12 to be evaluated is about 500 nm. The metal sintered layer 20 is a silver sintered layer having a thickness of 1.5 μm.
[0035] For comparison, cross-section evaluation sample 8 was prepared in the same manner as in the method for preparing a cross-section evaluation sample according to the embodiment, except that paste material 21 was not sintered. Metal paste layer 80 was a silver paste layer.
[0036] Next, the evaluation surfaces 1a and 8a of the cross-sectional evaluation samples 1 and 8 were observed by a scanning electron microscope. In addition, the band edge emission intensities of the evaluation surfaces 1a and 8a of the cross-sectional evaluation samples 1 and 8 were measured by a CL method.
[0037] Fig. 11 is a diagram showing the evaluation results of a cross-sectional evaluation sample 1 having a metal sintered layer 20 formed on a surface 10a. Fig. 11(a) shows an SEM image of the evaluation target surface 1a, and Fig. 11(b) shows the band edge emission intensity of the evaluation target surface 1a. In Fig. 11(b), the area shown in white indicates the area where band edge emission was observed.
[0038] Fig. 12 shows the evaluation results of a cross-section evaluation sample 8 having a metal paste layer 80 formed on the surface 10a. Fig. 12(a) shows an SEM image of the evaluation surface 8a, and Fig. 12(b) shows the band-edge luminescence intensity of the evaluation surface 8a. In Fig. 12(b), the area shown in white indicates the area where band-edge luminescence was observed.
[0039] Fig. 13 is a graph comparing band edge emission intensities. In Fig. 13, the horizontal axis indicates the position in the direction perpendicular to surface 10a, and the vertical axis indicates the band edge emission intensity normalized with the peak value of the band edge emission intensity of cross-sectional evaluation samples 1 and 8. In Fig. 13, the solid line indicates the result of cross-sectional evaluation sample 1, and the dashed line indicates the result of cross-sectional evaluation sample 8.
[0040] As shown in Fig. 11(a), in the cross-sectional evaluation sample 1, there is no gap at the interface between the evaluation target film 12 and the metal sintered layer 20, and it is found that the metal sintered layer 20 is in close contact with the evaluation target film 12. As shown in Fig. 11(b) and Fig. 13, in the cross-sectional evaluation sample 1, almost no band edge emission is observed in the metal sintered layer 20. These results show that it is possible to reduce the amount of abnormal signals detected when evaluating the evaluation target surface 1a of the cross-sectional evaluation sample 1.
[0041] 12(a), in the cross-sectional evaluation sample 8, the metal paste layer 80 is granular, and many voids are formed at the interface between the evaluation target film 12 and the metal paste layer 80. As shown in FIG. 12(b) and FIG. 13, in the cross-sectional evaluation sample 8, band edge emission is observed in the metal paste layer 80. These results indicate that the amount of abnormal signals detected when evaluating the evaluation target surface 8a of the cross-sectional evaluation sample 8 cannot be sufficiently reduced.
[0042] Next, damage that occurs on the surface 10a of the structure 10 when the metal thin film 90 is formed on the surface 10a by sputtering was evaluated.
[0043] First, a gallium nitride epitaxial substrate (hereinafter simply referred to as "epi-substrate") was prepared. Next, the CL spectrum of the surface of the epi-substrate was measured. Next, a gold film, which is a thin metal film 90, was formed on the surface of the epi-substrate by sputtering. The gold film had a thickness of several nm. Next, the CL spectrum of the surface of the epi-substrate on which the gold film was formed was measured. That is, the CL spectrum of the surface of the epi-substrate was measured before and after the gold film was formed by sputtering.
[0044] Figure 14 is a graph comparing CL spectra. In Figure 14, the horizontal axis represents wavelength [nm], and the vertical axis represents the signal intensity of the CL spectrum on the surface of the epitaxial substrate normalized by the peak value of the emission intensity around a wavelength of 360 nm.
[0045] As shown in Fig. 14, the CL spectrum of the surface of the epitaxial substrate after the gold film is formed by sputtering has an increased signal intensity at a wavelength of about 560 nm compared to the CL spectrum of the epitaxial substrate before the gold film is formed by sputtering. The signal at a wavelength of about 560 nm is a signal caused by defects, and is also called yellow luminescence. From this result, it is considered that forming a metal thin film 90 on the surface of the epitaxial substrate by sputtering causes damage (alteration) to the surface of the epitaxial substrate.
[0046] Although the embodiments have been described in detail above, the present invention is not limited to the specific embodiments, and various modifications and changes are possible within the scope of the claims. [Explanation of symbols]
[0047] 1, 8, 9 Cross-sectional evaluation samples 1a, 8a, 9a Evaluation surface 10 Structure 10a surface 10b side 11 Substrate 12. Film to be evaluated 20 Metal sintered layer 21 Paste material 30 Metal Sheet 80 Metal paste layer 90 Metallic Thin Film
Claims
1. Preparing a structure having a first surface and a second surface connected to the first surface; applying a paste material containing metal nanoparticles onto the first surface; sintering the paste material applied onto the first surface to form a metal sintered layer; A step of polishing the second surface of the structure on which the metal sintered layer is formed to form an evaluation target surface; The pretreatment method according to claim 1,
2. The thickness of the metal sintered layer is 1 μm or more. The pretreatment method according to claim 1 .
3. The metal nanoparticles include at least one metal selected from the group consisting of gold, silver, chromium, cobalt, copper, iron, palladium, platinum, tantalum, tin, titanium, and zinc. The pretreatment method according to claim 1 or 2.
4. Preparing a structure having a first surface and a second surface connected to the first surface; applying a paste material containing metal nanoparticles onto the first surface; sintering the paste material applied onto the first surface to form a metal sintered layer; A step of polishing the second surface of the structure on which the metal sintered layer is formed to form an evaluation target surface; A method for preparing a cross-sectional evaluation sample comprising the steps of:
5. The cross-section evaluation sample is used to evaluate the chemical state of the second surface by irradiating it with an electron beam. A method for producing a cross-section evaluation sample according to claim 4.
Citation Information
Patent Citations
Observation method for use in scan-type electronic microscope
JP1993003012A